Small fish, big discoveries: zebrafish shed light on microbial biomarkers for neuro-immune-cardiovascular health - Sree Kumar, Hemaa; Wisner, Alexander S.; Refsnider, Jeanine M.; Martyniuk, Christopher J.; Zubcevic, Jasenka (Frontiers in Physiology, 2023)
Zebrafish (Danio rerio) have emerged as a powerful model to study the gut microbiome in the context of human conditions, including hypertension, cardiovascular disease, neurological disorders, and immune dysfunction. Here, we highlight zebrafish as a tool to bridge the gap in knowledge in linking the gut microbiome and physiological homeostasis of cardiovascular, neural, and immune systems, both independently and as an integrated axis. Drawing on zebrafish studies to date, we discuss challenges in microbiota transplant techniques and gnotobiotic husbandry practices. We present advantages and current limitations in zebrafish microbiome research and discuss the use of zebrafish in identification of microbial enterotypes in health and disease. We also highlight the versatility of zebrafish studies to further explore the function of human conditions relevant to gut dysbiosis and reveal novel therapeutic targets.